The Effect of Internal Control Systems and Inventory Information Systems on the Effectiveness of Inventory Stock Recording - Tasya Khairinisa; Nur Zeina Maya Sari; Dian Widyantini (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze the effect of internal control system implementation and inventory information system on the effectiveness of inventory stock recording at PT Pindad (Persero) BUMN Bandung. Managing inventory effectively is a critical operational foundation for manufacturing companies to avoid overstocking or stockouts. The internal control system provides a structured mechanism to safeguard corporate assets and ensure financial report reliability, while the inventory information system minimizes manual human errors through integrated databases. The dependent variable, effectiveness of inventory stock recording, reflects the system's capacity to maintain accurate, timely, and complete inventory records. This study applied a quantitative approach with descriptive and verification methods. Questionnaires were distributed via purposive sampling to a total sample of 33 respondents across the Rendalprod, General, Engineering, and Production departments under the Industrial Engineering Manufacturing division . Data analysis was performed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) via SmartPLS version 4 to evaluate the outer measurement model and inner structural model. The structural model testing results revealed that the internal control system has a positive but non-significant influence on the effectiveness of inventory stock recording. Conversely, the inventory information system exerts a positive, strong, and statistically significant effect on the effectiveness of inventory stock recording. These empirical findings highlight that maximizing technical information system optimization and aligning system data with physical inventory counts are essential strategies to elevate stock record precision within national strategic state-owned enterprises.